Scientific Translation and its Social Functions: a Descriptive-Functional Approach to Scientific Textbook Translation in China - Fan Xiangtao (JoSTrans: The Journal of Specialised Translation)
From 1900 to 1911, a large number of scientific textbooks for primary and secondary schools from foreign countries were translated into Chinese for the purpose of introducing science education in China. These translated books have since exerted a great influence on the Chinese society. Adopting the descriptive-functional methodology and with reference to statistical analysis, this paper describes and examines this translation phenomenon, including the historical-cultural context which affected and constrained the translation selections of such textbooks, the translating process, and their criticism and social functions. The paper concludes that translated scientific textbooks influence both the surface and deep structures of Chinese traditional culture, and that their criticism should be integrated into the cultural background in order that the criticism becomes more inclusive, scientific and objective.